Genetic diversity of Aedes aegypti populations from Kisumu and Busia counties, western Kenya, and their vector competence for chikungunya virus - Victor O. Anyango; Solomon Langat; Francis Mulwa; James Mutisya; Hellen Koka; Collins Okoyo; Edith Chepkorir; Samson Konongoi; Anncarol Karanja; Glennah Kerubo; Rosemary Sang; Joel Lutomiah (PLoS ONE, 2025)
Aedes aegypti (Ae. aegypti) is the primary vector of several arboviruses, including dengue virus (DENV), chikungunya virus (CHIKV), yellow fever virus (YFV), and Zika virus (ZIKV). This vector is widespread globally in tropical and subtropical areas but also found in temperate areas. Kenya experienced its first chikungunya outbreak in Lamu County in 2004, followed by subsequent outbreaks in Mandera in 2016 and Mombasa in 2017. Despite the presence of Ae. aegypti in Kisumu and Busia counties, no outbreaks of chikungunya fever have been reported in these two western Kenya counties. To investigate this phenomenon, we collected Ae. aegypti mosquitoes from the county headquarter towns of Kisumu and Busia. The mosquitoes were reared under controlled laboratory conditions, and their genetic diversity assessed using COI gene sequences. Additionally, neutrality tests, including Tajima’s D and Fu’s FS, were subsequently performed to infer evolutionary dynamics. The mosquitoes were then evaluated for their ability to transmit CHIKV by challenging laboratory-reared F1 generations of field-collected mosquitoes with an infectious blood meal containing CHIKV. Genetic analysis revealed the presence of both Ae. aegypti subspecies, (Ae. aegypti aegypti [Aaa] and Ae. aegypti formosus [Aaf]) in the two western Kenya counties, with Aaf being dominant (19:8 for Kisumu samples and 25:6 for Busia samples). The populations exhibited high haplotype diversity (0.96011 in Kisumu and 0.93763 in Busia) and low nucleotide diversity (0.00913 in Kisumu and 0.00757 in Busia), indicating significant genetic polymorphism at the loci examined. Additionally, negative neutrality tests, including Tajima’s D (-1.87530 for Kisumu and -1.09547 for Busia) and Fu’s FS (-10.223 for Kisumu and -15.249 for Busia), coupled with a smooth mismatch distribution, suggest that recent evolutionary events may have significantly shaped the genetic structure of these populations. The assessment of vector competence of Ae. aegypti populations from Kisumu and Busia counties revealed their capacity to support CHIKV transmission. Specifically, we demonstrated infection, dissemination, and transmission rates of 55.2%, 85.5%, and 27.1% for Kisumu, and 57.8%, 71.8%, and 25% for Busia, respectively. However, statistical analysis indicated no significant difference in vector competence between the two populations. These findings underscore the uniform potential of Ae. aegypti mosquitoes from both Kisumu and Busia to facilitate the spread of CHIKV, highlighting the need for consistent surveillance and vector management strategies across these regions.